Evaluating clinician experience in value-based health care: the development and validation of the Clinician Experience Measure (CEM) - Reema Harrison; Elizabeth Manias; Louise Ellis; Laurel Mimmo; Ramesh Walpola; Ben Roxas-Harris; Timothy Dobbins; Rebecca Mitchell; Sharyn Cowie; Glen Maberly; Catherine Chan; Liz Hay (BMC, 2022)
Abstract Background Clinicians' experiences of providing care constitute an important outcome for evaluating care from a value-based healthcare perspective. Yet no currently available instruments have been designed and validated for assessing clinicians' experiences. This research sought to address this important gap by developing and validating a novel instrument in a public health system in Australia. Methods A multi-method project was conducted using co-design with 12 clinician leaders from a range of NSW Health Local Health Districts to develop the Clinician Experience Measure (CEM). Validity and reliability analyses were conducted in two stages, first assessing face and content validity with a pool of 25 clinicians and then using psychometric analysis with data from 433 clinicians, including nurses, doctors and allied health and representing all districts within one jurisdiction in Australia. Results Data gathered from 25 clinicians via the face and content validity process indicated that the initial 31-items were relevant to the range of staff employed in the NSW state health system, with minor edits made to the survey layout and wording within two items. Psychometric analysis led to a rationalised 18-item final instrument, comprising four domains: psychological safety (4-items); quality of care (5-items); clinician engagement (4-items) and interprofessional collaboration (5-items). The 18-item four-factor model produced a good fit to the data and high levels of reliability, with factor loadings ranging from .62 to .94, with Cronbach's alpha (range: .83 to .96) and composite reliability (range: .85 to .97). Conclusions The CEM is an instrument to capture clinicians' experiences of providing care across a health system. The CEM provides a useful tool for healthcare leaders and policy makers to benchmark and assess the impact of value-based care initiatives and direct change efforts.